2011
DOI: 10.4103/1319-3767.77237
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetic gastroparesis

Abstract: Symptoms suggestive of gastroparesis occur in 5% to 12% of patients with diabetes. Such a complication can affect both prognosis and management of the diabetes; therefore, practicing clinicians are challenged by the complex management of such cases. Gastroparesis is a disorder characterized by a delay in gastric emptying after a meal in the absence of a mechanical gastric outlet obstruction. This article is an evidence-based overview of current management strategies for diabetic gastroparesis. The cardinal sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Most patients improved glycemic control and symptoms by conventional treatment of western medicine [16, 17]. However, these managements are far from clinical satisfaction [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients improved glycemic control and symptoms by conventional treatment of western medicine [16, 17]. However, these managements are far from clinical satisfaction [18].…”
Section: Discussionmentioning
confidence: 99%
“…Current pieces of research have found that smooth muscle degeneration in DGP is caused by multiple factors, including autonomic nervous dysfunction, hyperglycemia, gastrointestinal hormone secretion disorder, abnormalities of interstitial cells of Cajal (ICC), and vascular lesions [1114]. Based on blood glucose control, the available treatment options of modern medical treatment include nutritional support, improvement of gastric emptying using prokinetics, symptom control, and use of a gastric electric stimulator [15, 16]. The increasing number of drugs under development with different mechanisms of action improves clinical symptoms, whereas they are far from clinical satisfaction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes often complain of the symptoms of upper GI disorders without any apparent cause. Particular tests could show a delay in emptying the stomach or diabetic gastroparesis, which commonly occur in people with DM types 1 and 2 [9]. Gastroparesis itself has been defined as the delayed emptying of the stomach characterized by a rapidly satiated, full feeling in the stomach, nausea, vomiting, bloating, and upper abdominal pain.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Routine Western medicine therapy for gastroparesis includes prokinetic agents, gastric pacemaking, and surgery. However, side effects like extrapyramidal symptoms, cardiac arhythmia, local infection, malnutrition, and weight loss are inevitable [ 5 ]. Acupuncture, moxibustion and massage are complementary alternative medicine techniques with reliable efficacy and fewer side effects, and are quickly becoming more widely used world-wide.…”
Section: Introductionmentioning
confidence: 99%